2020
DOI: 10.1186/s13046-020-1537-9
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of ABCB1-related multidrug resistance by ERK5-IN-1

Abstract: Background: Inhibition of ABC transporters is considered the most effective way to circumvent multidrug resistance (MDR). In the present study, we evaluated the MDR modulatory potential of ERK5-IN-1, a potent extracelluar signal regulated kinase 5 (ERK5) inhibitor. Methods: The cytotoxicity and MDR reversal effect of ERK5-IN-1 were assessed by MTT assay. The KBv200inoculated nude mice xenograft model was used for the in vivo study. Doxorubicin efflux and accumulation were measured by flow cytometry. The modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Chemotherapy is introduced to breast cancer treatment as neoadjuvant chemotherapy aiming to shrink locally advanced tumors before surgery, as adjuvant chemotherapy after surgical intervention to eliminate residual cancer cells, as well as a treatment option for advanced metastatic breast cancers [ 49 ]. Moreover, inhibition of EGFR signaling is associated with decreased drug efflux activity [ 50 ]. In the case of TNBC, which does not respond to hormonal and targeted therapy, the main line of treatment is chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is introduced to breast cancer treatment as neoadjuvant chemotherapy aiming to shrink locally advanced tumors before surgery, as adjuvant chemotherapy after surgical intervention to eliminate residual cancer cells, as well as a treatment option for advanced metastatic breast cancers [ 49 ]. Moreover, inhibition of EGFR signaling is associated with decreased drug efflux activity [ 50 ]. In the case of TNBC, which does not respond to hormonal and targeted therapy, the main line of treatment is chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ERK5 silencing also potentiates doxorubicin and cisplatin therapies in malignant mesothelioma cells [48], or doxorubicin, cyclophosphamide, and paclitaxel in TNBC cells [49]. The mechanism by which ERK5 inhibition sensitizes several types of cancer cells remains to be described, although it has been suggested that it could be due to inhibition of some of the ABC transporters [50]. Since we found that pharmacologic inhibition of the NF-κB pathway (IKKβ inhibitor BAY-117082) also potentiated the cytotoxic effect of paclitaxel and carboplatin in EC cells, it is plausible that NF-κB inhibition may mediate the sensitization of EC cells to chemotherapy exerted by ERK5 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Animal study was performed as previously described [ 44 , 45 ]. The BACB/C nude mice xenograft models were used for the in vivo study.…”
Section: Methodsmentioning
confidence: 99%